Prevalence and Correlational Factors of Suicidal Ideation and Suicide Attempts Among Chinese Adolescents - Yan, Yan; Gai, Xiaosong (Frontiers in Psychology, 2022)
This study’s purpose was to (1) determine the prevalence of suicidality (i.e., suicidal ideation or suicide attempts) among adolescents in a city in Northeast China and (2) identify the correlational factors among adolescents with suicidality. A total of 69,519 adolescents from grades 5 to 12 in a city in Northeast China participated in the online investigation. Students completed a structured questionnaire to report their demographic information, psychological characteristics, and suicidality. Univariable and multivariable logistic regressions were applied to determine significant correlational factors associated with suicidal ideation (SI) and suicide attempts (SA). The prevalence of SI and SA among adolescents in the past 12 months was 13% and 4.8%, respectively. Multivariable logistic regression analyses found that the potential risk factors for SI and SA included female, non-nuclear family, higher subjective socioeconomic status, meaningless in life, depression, bullying perpetrator, negative parental rearing styles, lower self-esteem scores, hopelessness, and stressful life events. In order to improve the accuracy of suicide risk identification, a cumulative risk index was used. With the increase in the number of cumulative risks, the risk of SI and SA also increased. So the cumulative risk index was very valuable. The total prevalence of SI and SA among primary and middle school students was high. Preventive measures could be implemented according to the risk factors.